Finance for non-finance people - Goel, Sandeep (London Routledge, 2025)
This book makes sense of the finance world from a non-finance perspective. It introduces, explains and demystifies essential ideas of business finance to those who do not have a financial background or training. The book delineates the financial workings of businesses and offers an overview of financial management in a global context. The volume: Discusses fundamental concepts and applications of accounting and finance at the global level Contains effective tools for financial analysis.